IMPLEMENTASI PEMBIMBINGAN DAN PENGAWASAN PK BAPAS TERHADAP PERUBAHAN PERILAKU KLIEN PEMASYARAKATAN YANG MELAKUKAN PELANGGARAN HUKUM KEMBALI (Studi kasus di Balai Pemasyarakatan Kelas II Kediri) - Idha Wening Setiasih; Nurbaedah Nurbaedah (Universitas Islam Kadiri, 2023)
The purpose of this study was to analyze the implementation of the guidance and supervision of Probation Officer according to Law Number 12 of 1995 concerning Corrections and Regulation of the Government of the Republic of Indonesia Number 31 of 1999 concerning the Coaching and Guidance of Correctional Assisted Citizens against changes in the behavior of correctional clients who break the law again, to analyze the obstacles faced by the Probation Officer in guiding and supervising correctional clients who break the law again. The location of this study is the Class II Penitentiary (Bapas) Kediri which is located at Penanggungan street, no. 19, Kediri City, East Java, with a total of 13 respondents using the purposive sampling method with qualitative data analysis and data collection techniques using primary data and secondary data obtained by structured interviews, in-depth interviews, observation, and documentation. The result of this study is that the guidance and supervision of Probation Officer on the behavior of correctional clients has been effective as seen from Law Number 12 of 1995 concerning Corrections and Regulation of the Government of the Republic of Indonesia Number 31 of 1999 concerning the Coaching and Guidance of Correctional Assisted Citizens because almost all of these regulations have been carried out and implemented by the Probation Officer, However, when viewed from the behavior of correctional clients, the guidance and supervision of the Probation Officer has not been fully effective because there has been no change in the behavior of correctional clients who are still breaking the law.. The factors that become obstacles for the Penitentiary (Bapas) Kediri in carrying out guidance tasks for correctional clients are a) Penitentiary regulations, b) Penitentiary personnel, c) Infrastructure, d) Personal, from correctional clients and the family., and e) Cost.